2013
DOI: 10.1055/s-0033-1357065
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and ex vivo toxicity screening for predicting toxicological effects of synthetic carbon black nanoparticles in humans

Abstract: The aim of this study was to compare the effects of synthetic carbon black nanoparticles (CBNP) with and without polycyclic aromatic hydrocarbons adsorbed to their surface. Printex®90 and acetylene soot particles as well as particles covered with either benzo[a]pyrene (BaP) or nitroanthracene (NA) were tested in human pulmonary cell lines (16HBE14o-, Calu-3, A549) and precision cut lung slices (PCLS) of mice, rats and humans using a wide concentration range. Particle size distribution in the cell culture mediu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Over the past decade, researchers have carried out both in vitro and in vivo cytotoxicity assessments of CB-NPs on various human cells. [15][16][17][18][19][20][21][22][23][24] It has been found that CB-NPs sometimes appeared to be nontoxic or even highly hazardous. These varying results were likely dependent on the synthesis of CB-NPs.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, researchers have carried out both in vitro and in vivo cytotoxicity assessments of CB-NPs on various human cells. [15][16][17][18][19][20][21][22][23][24] It has been found that CB-NPs sometimes appeared to be nontoxic or even highly hazardous. These varying results were likely dependent on the synthesis of CB-NPs.…”
Section: Introductionmentioning
confidence: 99%